Informal trade in livestock and livestock products - Grace, Delia; Little, P. (World Organisation for Animal Health, 2020)
Informal trade in livestock and livestock products is of special concern because of the risk of spreading animal and human diseases. At the same time, informal trade can contribute to people’s livelihoods and food security, especially in lowand middle-income countries. Informal trade may involve legal or illegal products. It may be domestic (or internal) or involve neighbouring countries; it may take place within a region or between distant countries. Entrepôt trade (or ‘re-exports’) is a significant form of informal trade in livestock products. Pastoral mobility often entails movement across boundaries for trade and much of this is also informal. There are important economic, social, political, and environmental drivers for informal trade which make it difficult to eliminate. Informal livestock trade may be largely ignored by the authorities, implicitly encouraged, made less attractive, forcibly suppressed, or actively engaged with, in an attempt to mitigate its risks and enhance its benefits. To identify the optimal management approach, it is crucial to understand the importance and characteristics of informal trade, its benefits and risks, and the feasibility and cost-effectiveness of different strategies to address it. The authors describe a case study from East Africa to explore some of the issues raised by informal trade.